The use of filter-feeding fish (Clarias gariepinus and Oreochromis mossambicus) to remove microalgae from brewery effluent treatment ponds - Nombembe, Lwazi (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2019)
The removal of microalgae from high rate algal ponds (HRAP) in waste-water treatment systems remains a constraint to their use in effluent treatment systems. Conventional algae harvesting methods often have high energy demands, take up lots of space, are expensive to operate or are time consuming. The aim of the study was to determine if fish such as Clarias gariepinus and Oreochromis mossambicus, could be used to remove microalgae from waste-water treatment ponds (in the absence/presence of a flocculent in the former and in the absence or presence of pH moderation in the latter), and to investigate the subsequent influence of algae concentration on several water quality parameters. The age of Clarias gariepinus (3-12 months) had a positive relationship with the distance between gill rakers (98.27 to 163.34 μm; y=90.576+4.823*x: R²=0.549; F(1,18)=21.867; p<0.001) and these data suggested that these fish might be efficient at removing algae from HRAP effluent. However, this was not the case, even with flocculent application (but this result might have been confounded by very high pH readings, at which flocculation is less likely to occur). Oreochromis mossambicus removed some of this algae, but the pH was too high for tilapia culture. It was not possible to moderate the increase in pH by keeping tanks in the dark and thus preventing photosynthesis; but pH fluctuation in HRAP effluent could be moderated using CO2 sparging in an attempt to make the environment more hospitable for tilapia (the average pH that was moderated with CO2 was 8.43±0.06, whereas the unmoderated average was 10.65±0.06). However, pH moderation using CO2 sparging did not increase the rate at which algae were removed by O. mossambicus; rather, it compromised O2 concentration which dropped to 4.17±1.26 mg/l after five hours of CO2 sparging, whereas it increased to 20.50±1.41 mg/l in treatments with unadjusted pH over the same period. Fish can be used to remove algae from treated effluent, and Oreochromis mossambicus remains a recommended species. Future work needs to investigate moderating fluctuations in pH and O2 concentration to further facilitate this method of algae removal.
Keywords: Clarias gariepinus -- Food; Mozambique tilapia -- Food; Water -- Purification -- South Africa; Algae -- Biotechnology -- South Africa; Microalgae -- Biotechnology-- -- South Africa; Brewery waste -- South Africa; Fish culture -- South Africa